Neuroanatomic Correlates of Distance and Direction Processing During Cognitive Map Retrieval - Faulmann, Igor; Descloux, Virginie; Saj, Arnaud; Maurer, Roland (Frontiers in Behavioral Neuroscience, 2020)
Navigating towards a goal and mentally comparing distances and directions to landmarks are processes requiring to read information off the memorized representation of the environment, i.e., the cognitive map. Brain structures in the medial temporal lobe, in particular, are known to be involved in the learning, storage and retrieval of cognitive map information, which is generally assumed to be in allocentric form, whereby pure spatial relations (i.e., distance and direction) connect locations with each other. We recorded fMRI activity while participants were submitted to a variant of a neuropsychological test (the Cognitive Map Reading Test) originally developed to evaluate the performance of brain-lesioned patients, and in which participants have to compare distances and directions in their mental map of their home town. Our main results indicated posterior parahippocampal, but not hippocampal, activity, consistent with a task involving spatial memory of places learned a long time ago; left parietal and left frontal activity, consistent with the distributed processing of navigational representations; and, unexpectedly, cerebellar activity, possibly related to the role of the cerebellum in the processing of (here, imaginary) self-motion cues. In addition, direction, but not distance, comparisons elicited significant activation in the posterior parahippocampal gyrus.